Five new species of the genus Tetra Keifer (Acari: Eriophyoidea) from China - Xue, Xiao-Feng; Hong, Xiao-Yue Hong (Zootaxa, 2005)
In this paper, five new species of the genus Tetra from China are described and illustrated. They are: Tetra suspensae n. sp. on Forsythia suspensa (Thunb.) Vahl; Tetra lobatae n. sp. on Pueraria lobata (Willd.) Ohwi; Tetra japonicae n. sp. on Sophora japonica L.; Tetra formosae n. sp. on Lespedeza formosa (Vog.) Koehne and Tetra lycopersici n. sp. on Lycopersicon esculentum Mill. A key to the species of Tetra from China is provided.